Pengembangan E-LKPD Berbasis Multimedia Menggunakan Zep Quiz pada Materi Jurnal Penyesuaian untuk Meningkatkan Keterlibatan Belajar Siswa: Development of Multimedia-Based Electronic Student Worksheets (E-LKPD) Using Zep Quiz on the Topic of Adjusting Entries to Enhance Student Learning Engagement - Ismiyatinur Azizah; Rochanda Wiradinata; Rusdiyana Rusdiyana (ITScience (Information Technology and Science), 2026)
Learning about adjusting entries in Vocational High Schools (SMK) requires the ability to identify accounts, calculate amounts, and construct accurate journal entries. A needs analysis revealed that students struggle to grasp adjustment procedures and require repeated practice accompanied by immediate feedback. Conventional teaching materials tend to render students passive and disengaged. Consequently, there is a need for interactive digital media that integrates content, practice exercises, and evaluation. A multimedia-based Electronic Student Worksheet (E-LKPD) integrated with the